0072 A Mexican Spanish Version of the Insomnia Severity Index. (25th May 2022) - Granados, Karla; Begay, Tommy; Valencia, Dora; Delgadillo, Marcos; Ghani, Sadia; Molina, Patricia; Alfonso-Miller, Pamela; Fernandez-Mendoza, Julio; Wills, Chloe; Grandner, Michael
Abstract: Introduction: Data were collected for the Insomnia Severity Index (ISI). To ensure the validity of study subject responses, the ISI was translated into Mexican Spanish by a bilingual research study team, based on a previous Spanish translation. It was then administered to study subjects in their preferred language. Methods: Data were collected from a sample of N=100 individuals of Mexican Descent in Nogales, Arizona, at the US-Mexico border. The Insomnia Severity Index (ISI) is a 7-item scale that quantifies the degree to which an individual experiences insomnia symptoms. A Spanish translation already exists, but this had not been previously localized to Mexican Spanish. To localize the measure, the following procedure was followed: (1) a bilingual community member edited the translation; (2) a certified medical translator edited the revised items; (3) a focus group of N=5 bilingual community members made contextual edits to the new measure; (4) a back-translation was performed; (5) an additional bilingual focus group examined the final version for compatibility; and (6) the medical translator certified the accuracy of the final version. As a result of this process, text edits to items 4 and 6 were made to accomplish the localization (the other items remained unchanged). T-tests examined differences between those who completed the measure in Mexican Spanish vs English. Results: Of the N=100 survey respondents, N=42 completed the ISI in Spanish. Those who completed the ISI in Spanish reported significantly lower overall scores (8.2 vs 9.8, p=0.048). No significant differences were seen for individual items regarding early morning awakenings (p=0.13), satisfaction (p=0.71), interference with daily functioning (p=0.29), whether sleep problems are noticeable (p=0.06), and worry/distress about sleep (p=0.14). However, those completing the measure in Spanish reported lower scores on items regarding difficulty falling asleep (p=0.03) and staying asleep (p=0.001). Conclusion: When adapting the ISI to a Spanish-speaking population at the US-Mexico border, modifications were made to the existing Spanish translation to improve linguistic and cultural appropriateness. Support (If Any):